2015
DOI: 10.1186/1476-069x-14-12
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of in utero low-level arsenic exposure and fetal growth using biometric measurements extracted from fetal ultrasound reports

Abstract: BackgroundEarly life exposure to arsenic is associated with decreased birth weight in highly exposed populations but little is known about effects of low-level arsenic exposure on growth in utero.MethodsUsing a sample of 272 pregnancies from New Hampshire we obtained biometric measurements directly from fetal ultrasound reports commonly found in electronic medical records. We used information extraction methods to develop and validate an automated approach for mining biometric measurements from the text of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 56 publications
2
29
2
Order By: Relevance
“…Similar to our findings, several epidemiological studies have noted that embryonic arsenic exposures from maternal drinking water reduces birth weight and weight gain in children (Bloom et al, 2014; Davis et al, 2015; Hopenhayn et al, 2003; Kile et al, 2016). For example, children born to mothers in arsenic-exposed villages in Taiwan were 29g lighter than those from non-exposed villages (Yang et al , 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, several epidemiological studies have noted that embryonic arsenic exposures from maternal drinking water reduces birth weight and weight gain in children (Bloom et al, 2014; Davis et al, 2015; Hopenhayn et al, 2003; Kile et al, 2016). For example, children born to mothers in arsenic-exposed villages in Taiwan were 29g lighter than those from non-exposed villages (Yang et al , 2003).…”
Section: Discussionsupporting
confidence: 92%
“…4951 Some have speculated that As’s vascular impacts could affect the placenta by leading to placental insufficiency and intrauterine growth retardation, thus potentially underlying As-related effects on fetal growth and birth weight. 5761 While it is unclear whether As-related changes in a mother’s vascular health may affect her child’s health, our structural equation models suggest that As’s effects on biomarkers of maternal endothelial function may in turn mediate similar changes in these same biomarkers in infants. Nonetheless, the long-term impacts of these changes have yet to be explored.…”
Section: Discussionmentioning
confidence: 88%
“…Still, given the novelty of this result additional confirmation is necessary and so we are reluctant to speculate with respect to biologic mechanism. U.S. investigators recently reported that smaller head size on ultrasound was associated with higher maternal urine iAs for girls, but not for boys, in a New Hampshire population with exposure to 0 – 9.3 μg/L drinking water iAs [84]. Thus sex-specific vulnerabilities may be important to the impact of iAs on growth in utero .…”
Section: Discussionmentioning
confidence: 99%